A web‐based training approach for the structural steel design. Issue 3 (11th October 2010) - Serrano‐Lopez, Miguel; López‐Colina, Carlos; López‐Gayarre, Fernando; Armstrong, Sue
Abstract Fortunately the design processes of steel buildings across Europe is eventually covered by a unified code: The Eurocode 3: "Design of steel structures." Nevertheless, although Eurocodes will soon become mandatory documents, designs will not be standardized because each country has a set of National Annexes which must be taken into account when designing in that particular country. Furthermore, every country also has its own body of non‐conflicting complementary information. A problem then arises when engineers need to produce designs in other European countries, either for a company based in one state or as individuals. Also, allowing engineers time out of the office for attendance at the intensive training courses which are required for earning experience on the new codes of design, frequently represents an obstacle for their employers. In an attempt to solve these problems, a strong trans‐national partnership has been working to develop an ICT‐supported, flexible training approach to allow designers to apply Eurocodes in accordance with the national regulations and practices of different member states. The resulting material in seven languages shows how to design a typical building according to the different national contexts. The developed portal incorporates facilities for course presentation, forums, blogs and on‐line translation. The students thought that the portal was an effective tool that helped them to improve the quality and efficiency of their studies. In their opinion the web‐course is well structured and they found the forum for discussion and the web‐based tutoring system very helpful. © 2010 Wiley Periodicals, Inc. Comput Appl Eng Educ 21: 448–458, 2013